Ծաղկունքի վիմագրական ժառանգությունը - Ադամյան, Սուսաննա Խ.
ՀՀ Գեղարքունիքի մարզը հարուստ է պատմաճարտարապետական կոթողներով, որոնց թիվն ավելանում է տարեցտարի: XIX դարից սկսած` ուսումնասիրողները, լրացնելով իրար, հաղորդել են տեղեկություններ մարզի բնակավայրերի վերաբերյալ: Մեթոդներ և նյութեր․ Ընդհանուր առմամբ մարզի Գավառի, Մարտունու և Վարդենիսի տարածաշրջաններից հավաքվել և անցյալ դարի 70-ական թթ. «Դիվան հայ վիմագրության» հատորաշարում հրատարակվել է 1547 արձանագրություն: Բնական և մարդկային ազդեցությունից փրկելու նպատակով վերջին տասնամյակում մեր կողմից հավաքվել և ընդօրինակվել է ավելի քան 160 նորահայտ վիմագիր, միաժամանակ տեղում համեմատել ենք նախորդ հրատարակիչների վերծանությունները՝ կիրառելով համեմատական մեթոդը: Վերլուծություն․ Ուսումնասիրված վիմագրերը հիմնականում տապա-նագրեր են` երբեմն գրված անկանոն տառաձևերով: Դրանք հնարավորություն են տալիս հասկանալու բնակչության տեղաբաշխումն ու մշակութաjին զարգացումը: Արդյունքներ. Սույն ուսումնասիրությունը ներկայացնում է Սևանի տարածաշրջանի Ծաղկունք համայնքի միջնադարյան և նոր ժամանակաշրջանի կոթողներն իրենց վիմագրերով. գյուղի գլխավոր՝ Սբ Հարություն եկեղեցին, կառուցվել է XVII-XVIII դդ., պահպանվել է նաև Սբ Սարգիս եկեղեցին (VII դ.), մատուռներ, դրանց հարակից տարածքներում կա չորս գերեզմանատուն՝ խաչքարերով, տապանաքարերով: Ծաղկունքից մեզ հաջողվեց հավաքել և ընդօրինակել 19 հիշատակագրային բնույթի վիմագիր: The Gegharkunik region of RA is rich in historical and architectural monuments, the number of which increases every year as a result of archaeological excavations and earthworks. The first study was done back in the Middle Ages. Later, as a result of complicated military-political turns, some of the monuments were destroyed or damaged. Methods and materials: Already in the 19th century, after Eastern Armenia joined Russia, a huge attention was paid to the initiation of several branches of Armenology. During that time, the researchers by complementing each other, not only reported information about Armenian and non-religious settlements, but also collected Armenian lithographs, handwritten records, folklore, ethnographic, demographic, and historical materials. In the recent period, the study of the monuments has been comprehensive, especially the study of the inscriptions has given a new color to the study of the history and cultural values of Gegharkunik. In general, in the 70s of the last century 1547 inscriptions were recorded from Gavar, Martuni and Vardenis, which were summarized in the "Divan Armenian lithography" volume. Analysis: The studied inscriptions are mostly tombstones, sometimes written with irregular letter-forms. They provide insight into the population distribution and cultural development. Results: Over 160 newly discovered lithographs have been collected and copied by us in the last decade. In this article, we present the material evidences of the Tsaghkunk community of the Sevan region, the number of which reaches two dozen. Tsaghkunk is located in the northwestern part of the region, on the right bank of the Hrazdan River. The ancestors of the current residents migrated in 1828-1829 from historical Maku, Khoi, Van regions. The village is rich in medieval monuments. In XVII-XVIII centuries St Harutyun church was built by the head of the village, cemeteries with khachkars and tombstones have been preserved in its adjacent area and in different parts of the village.
Keywords: Հնագիտություն